TINJAUAN BERBAGAI KERETAKAN PADA POROS PROPELLER BALING-BALING KAPAL DENGAN MENGGUNAKAN PROSES NON DESTRUCTIVE TESTING - Andi Suadi; Fentje Abdul Rauf; Romels C A Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2016)
The aim of this study is to determine the damage of the propeller shaft using NON-DESTRUCTIVE-TEST method. The examination of the damage is conducted at ship of Anugerah Perdana 09which shaft’s diameter of 100mm and shaft’s length of 2,471mm, and Porodisa Vessel with diameter of 100 mm and length of 2,147 mm, there are two shaft, left and right, as the test object. Based on the examination result on both of the ship shafts, there are two damages. On Anugerah Perdana shaft, there is damage on the bottom side of the right keyway with length of 60 mm, while on Porodisa axis, there is one crack on the right keyway with length of 20 mm. Crack happended because on the shaft is because the ship bumping with reef or over-capacity. Keywords: Inspection, Crack or Defect Using Non-Destructive-Test